2015
DOI: 10.1016/j.bbamcr.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Cancer associated fibroblasts transfer lipids and proteins to cancer cells through cargo vesicles supporting tumor growth

Abstract: Fibroblasts are the most abundant cells in connective tissue and, with fibrillar extracellular matrix, form the structural scaffolding of organs. In solid tumors, interaction with cancer cells induces fibroblasts transdifferentiation into an activated form, which become a fundamental part of the tumor stroma. Within tumor microenvironment stromal and cancer cells engage a crosstalk that is mediated by soluble factors, cellcell contacts and extracellular vesicles trafficlking. Here we report that fibroblasts ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 36 publications
4
80
0
Order By: Relevance
“…In the present study, we employed a sequential centrifugation method to isolate MVs. Consistent with previous studies, MVs with diameters ranging from 100 to 600 nm were collected from various cancer cells (10,40). Because the MVs were observed to be transported to adjacent cells, our MV isolation method is appropriate for use in MV research.…”
Section: Discussionmentioning
confidence: 67%
“…In the present study, we employed a sequential centrifugation method to isolate MVs. Consistent with previous studies, MVs with diameters ranging from 100 to 600 nm were collected from various cancer cells (10,40). Because the MVs were observed to be transported to adjacent cells, our MV isolation method is appropriate for use in MV research.…”
Section: Discussionmentioning
confidence: 67%
“…However, recent studies revealed that fibroblasts, through exosome secretion, potentiate breast cancer cells and therapy resistance (34,35). Santi et al showed that CAFs transfer lipid and proteins to prostate and melanoma cancer cells through cargo vesicles that support tumor growth (36). Those studies revealed the important impact of stromal and tumor cell crosstalk through EV trafficking on tumor development; however, they did not evaluate the impact of the CAF environment.…”
Section: Anxa6 Lrp1 and Tsp1 Expression In Pda Is Mainly Driven Bymentioning
confidence: 96%
“…ANXA6+ (Annexin 6/LDL receptor-related protein-1/thrombospondin-1 complex) CAFs-secreted EVs enhanced tumor cell aggressiveness in pancreatic cancer (Leca et al, 2016). Fibroblast-derived exosomes induced mobilization, invasion (Luga et al, 2012), resistance to therapy and tumor recurrence in breast cancer (Boelens et al, 2014), while CAFs EVs-mediated transfer of proteins and lipids enhanced cancer proliferation rate of human prostate cancer and melanoma cell lines (Santi et al, 2015). The EVs transfer of surface receptors or intracellular material has been also associated with immunosuppressive and tumor-promoting functions.…”
Section: New Horizons Of Organoids Application: Modeling Evs Releasementioning
confidence: 99%